Cultura organizacional y eficiencia laboral de los trabajadores de la Empresa MPIG – Lima - 2021 - Lurita Dicción, Joel David (2022)
The objective of the research was to determine the relationship between organizational culture and efficiency in job performance in the company MPIG, Lima-2021 under a quantitative approach, an investigation was developed under a non-experimental cross-sectional design. The population consisted of 100 collaborators. Being a small sample, therefore, a sampling by convenience, the survey and Allen technique was used to collect the information. The results showed that the collaborators believe that the organizational culture requires attention- Regarding the variable efficiency in work performance, it was found that the collaborators presented an average level of commitment It was concluded that the adaptability dimension of the organizational culture variable does influence work commitment. Palabra Clave: Cultura organizacional, eficiencia laboral y colaborador. Keywords: organizational culture, work efficiency, collaborator